Vaccination trials in sheep against Chrysomya bezziana larvae using the recombinant peritrophin antigens Cb15, Cb42 and Cb48 - ., Sukarsih; Partoutomo, Sujitno; Wijffels, Gene; Voucoloco, Tony; Willadsen, Peter (Indonesian Animal Sciences Society, 2000)
Recombinant forms of a number of peritrophic membrane proteins from the screwworm fly Chrysomya bezziana have been assessed in vitro and in vivo for their efficacy as antigens in vaccination against the tissue-invasive, larval form of the parasite. The proteins included Cb15 and Cb42 expressed in Escherichia coli and Cb48 expressed in both Escherichia coli and Pichia pastoris. In all cases, the in vitro assays of larval growth on serum from vaccinated sheep failed to show inhibition of larval weight gain or any detrimental effect on larval survival relative to controls. Chrysomya bezziana Cb48 has a significant degree of sequence identity with the antigen PM48 from Lucilia cuprina. Feeding Lucilia cuprina larvae on antisera to Cb48 induced a small but statistically significant reduction in weight gain, as does feeding on antisera to PM48. In vivo, larvae feeding on sheep vaccinated with Escherichia coli-expressed Cb15 and Cb42 and Pichia pastoris-expressed Cb48 showed marginally greater weight gain and survival which was equal to or greater than that on non-vaccinated sheep. The significance of these observations is discussed. Â Key words: Chrysomya bezziana, recombinant antigen, peritrophin, vaccination